Untersuchung und Verbesserung des Stabilitätsverhaltens eines intensiven elektronengekühlten Teilchenstrahles in COSY - Kamerdzhiev, Vsevolod (Universität Dortmund, 2004)
The cooler synchrotron COSY provides proton and deuteron beams in the energy range of 45 MeV - 2,7 GeV and 75 MeV - 2,2 GeV, respectively, for precision experiments in medium energy physics. High beam quality is achieved by means of electron and stochastic cooling. Electron cooling is applied right after injection. However, in case of intense electron cooled proton (deuteron) beams fast particle losses due to transverse coherent beam oscillations are regularly observed. Unstable behaviour of the intense COSY beam, in particular of the electron cooled one, is investigated. The transverse stability is discussed in terms of transverse coupling impedances. Tune shifts due to high phase space densities are calculated. Possible cures of instabilities are analysed. Active damping of instabilities using a transverse feedback system is considered to be a suitable method to improve beam intensity and quality. A transverse damping system utilizing a pick-up, signal processing electronics, a power amplifier and a stripline deflector was designed, installed and successfully commissioned. Beam current, profile and Schottky spectra measurements with the feedback system turned on and off are presented. The feedback system allows to increase the cooled beam intensity by at least a factor of four when cooling and stacking of repeated injections is applied. Such a procedure is especially useful to increase the luminosity in internal experiments with the polarized beam which has a low injection intensity. For the experiments with unpolarized beams the significant increase of luminosity can be achieved without a decrease of the machine s duty factor. External experiments profit from the small diameter beams and the reduced halo.
Keywords: Elektronenkühlung; Electron cooling; Feedback; BTF; Strahlstabilität; Beam stability; BTF; 530